Infectious Transcripts from Cloned Genome-Length cDNA of Porcine Reproductive and Respiratory Syndrome Virus - Meulenberg, J. J. M. (American Society for Microbiology, 1998)
The 5′-terminal end of the genomic RNA of the Lelystad virus isolate (LV) of porcine reproductive and respiratory syndrome virus was determined. To construct full-length cDNA clones, the 5′-terminal sequence was ligated to cDNA clones covering the complete genome of LV. When RNA that was transcribed in vitro from these full-length cDNA clones was transfected into BHK-21 cells, infectious LV was produced and secreted. The virus was rescued by passage to porcine alveolar lung macrophages or CL2621 cells. When infectious transcripts were transfected to porcine alveolar lung macrophages or CL2621 cells, no infectious virus was produced due to the poor transfection efficiency of these cells. The growth properties of the viruses produced by BHK-21 cells transfected with infectious transcripts of LV cDNA resembled the growth properties of the parental virus from which the cDNA was derived. Two nucleotide changes leading to a unique PacI restriction site directly downstream of the ORF7 gene were introduced in the genome-length cDNA clone. The virus recovered from this mutated cDNA clone retained the PacI site, which confirmed the de novo generation of infectious LV from cloned cDNA. These results indicate that the infectious clone of LV enables us to mutagenize the viral genome at specific sites and that it will therefore be useful for detailed molecular characterization of the virus, as well as for the development of a safe and effective live vaccine for use in pigs.